Sosialisasi Pentingnya Pendidikan dan Literasi Anak Sekolah Dasar bagi Orang Tua di SDN 2 Junjang Wetan - Diantama, Suarifqi (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The low level of literacy among Indonesian society remains a challenge in improving the quality of human resources. Literacy is not only related to the ability to read and write but also includes the ability to understand, process, and effectively use information in daily life. One important factor influencing children’s literacy development is the role of parents in supporting the learning process at home. Therefore, this Community Service Program (PKM) aims to increase parents’ understanding and awareness of the importance of education and literacy for children from an early elementary school age. The activity was conducted at SDN 2 Junjang Wetan, Cirebon Regency, targeting parents of elementary school students. The implementation method involved socialization activities through interactive lectures, discussions, and question-and-answer sessions. The results showed that most participants initially had limited understanding of literacy concepts. After the activity, parents demonstrated increased awareness and gained knowledge of simple strategies to foster reading habits within the family environment.